2013
DOI: 10.3389/fnhum.2013.00178
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sarcasm detection in amyotrophic lateral sclerosis using ecologically valid measures

Abstract: Amyotrophic lateral sclerosis (ALS) is a rapidly progressive condition involving degeneration of both upper and lower motor neurons. Recent research suggests that a proportion of persons with ALS show a profile similar to that of frontotemporal dementia (FTD), with this group of ALS patients exhibiting social cognitive deficits. Although social cognitive deficits have been partially explored in ALS, research has yet to investigate such changes using ecologically valid measures. Therefore, this study aimed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
1
32
1
1
Order By: Relevance
“…The TASIT thus places fewer demands on executive function, a mechanism suggested to underlie previously reported deficits on the Happé tasks in ALS and FTD [18,45]. The current study failed to replicate the ALS group deficits reported previously on the TASIT [15]. At the individual level, some participants with ALS showed difficulty with the sarcastic exchanges, particularly on the SI-M component of the task where additional contextual cues, such as a visual cue or a scene prologue, were not available to aid interpretation (see Table 3).…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The TASIT thus places fewer demands on executive function, a mechanism suggested to underlie previously reported deficits on the Happé tasks in ALS and FTD [18,45]. The current study failed to replicate the ALS group deficits reported previously on the TASIT [15]. At the individual level, some participants with ALS showed difficulty with the sarcastic exchanges, particularly on the SI-M component of the task where additional contextual cues, such as a visual cue or a scene prologue, were not available to aid interpretation (see Table 3).…”
Section: Discussioncontrasting
confidence: 85%
“…Social cognition was assessed using a variety of measures used in previous studies of ALS but not together [13,15,18]: the Reading the Mind in the Eyes task (RME) [29]; three subtests of The Awareness of Social Inference Test (TASIT) [30] and three subtests of the Happé Cartoon and Written Scenarios tasks [31]. Executive function was assessed using the sorting and description trials of the Card Sorting Task of the Delis-Kaplan Executive Function Test (D-KEFS) [32]; the 'S' and 'C' trials of the modified Verbal Fluency Index (VFI) [33] and number of errors on the Brixton Test [34].…”
Section: Cognitive and Behavioural Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Un estudio con RM funcional demostró una mayor activación en el giro supramarginal derecho en pacientes con una sensibilidad alterada a claves sociales y emocionales 83,84 . También se han reportado déficits en la Teoría de la Mente y detección del sarcasmo 77,85,86 .…”
Section: Procesamiento Emocional Y Cognición Socialunclassified